Deep Eutectic Solvent Mediated Carbonylation of Amines and Alcohols by Using Dimethyl Carbonate: Selective Symmetrical Urea and Organic Carbonate Synthesis. Issue 41 (3rd November 2021) - Karimi, Farzaneh; Shariatipour, Monire; Heydari, Akbar
Abstract: This work presents one‐pot synthesis of symmetric organic carbonates and ureas by employing cheap and biodegradable deep eutectic solvent as the catalyst and reaction media. The effect of different reaction parameters such as temperature, DMC/amines and alcohols ratio and reaction time were investigated on the reaction efficiency. This new protocol provides a simple, fast, and sustainable approach and proceeds with high efficiency with aliphatic and aromatic amines and alcohols as well. Finally, applicability of this methodology was also examined for reaction of nucleophiles such as phenyl hydrazine and phenyl glycine with dimethyl carbonate. Interestingly, it was found that this reaction system obtained good yields of product for both of them. Abstract : an Environmentally‐ friendly methodology have been developed for the preparation of symmetric N, N ‐substituted ureas, organic carbonates, employing dimethyl carbonate as the green carbonylating agent and deep eutectic solvent as solvent/catalyst .Hydrazine and phenyl glycine was also successfully produced corresponding products with DMC under this condition.